Antimicrobial Peptides: Novel Source and Biological Function With a Special Focus on Entomopathogenic Nematode/Bacterium Symbiotic Complex - De Mandal, Surajit; Panda, Amrita Kumari; Murugan, Chandran; Xu, Xiaoxia; Senthil Kumar, Nachimuthu; Jin, Fengliang (Frontiers in Microbiology, 2021)
The rapid emergence of multi-drug resistant microorganisms has become one of the most critical threats to public health. A decrease in the effectiveness of available antibiotics has led to the failure of infection control, resulting in a high risk of death. Among several alternatives, antimicrobial peptides serve as potential alternatives to antibiotics to resolve the emergence and spread of multidrug-resistant pathogens. These small proteins exhibit potent antimicrobial activity and are also an essential component of the immune system. Though several AMPs have been reported and characterized, studies associated with their potential medical applications are limited. This review highlights the novel sources of AMPs with high antimicrobial activities, including the entomopathogenic nematode/bacterium (EPN/EPB) symbiotic complex. Additionally, the AMPs derived from insects, nematodes, marine organisms and the design of peptidomimetic antimicrobial agents that can complement the defects of therapeutic peptides have been used as a template.